Utilization of Artificial Intelligence (AI) in Completing Final Project at University Level - Asril, Lelly Zuyana; Fathira, Vina (Lectura : Jurnal Pendidikan, 2025)
Utilization of artificial intelligence (AI) technology is very important in helping English. This research aims to explore the utilization of artificial intelligence (AI) technology in helping English Literature Study Program students complete their final projects at university level. The research design used is a qualitative approach. The population in this study were students from the English Literature Study Program who were completing their final projects, with a sample of 10 students selected purposively. Data was collected through interviews using Google Form which contained five questions related to the utilization of AI in the final project. Data analysis was carried out by referring to the points contained in the interviews to answer the research objectives. The research results show that AI really helps students in completing their final projects, especially in terms of finding ideas, understanding concepts, and improving English language skills. However, some students also realize the limitations of AI in terms of source validity and accuracy of information provided. The conclusion of this research is that the utilization of AI must be balanced with critical evaluation of the information and sources provided to ensure the quality and acceptability of students’ final projects. This research provides a deeper understanding of the role of AI in supporting students’ final assignment completion, as well as the importance of vigilance in verifying information obtained from this technology.